Problematic Internet Use in Semarang Middle School Students - Wibowo, Mungin Eddy; Mulawarman, Mulawarman; Purwanto, Edy (KnE Social Sciences, 2019)
Problematic internet use (PIU) or problematic internet use is a maladaptive pleasure in using the internet excessively without self-control. This study aims to investigate the prevalence and risk factors for the level of problematic internet use held by high school students. To achieve this goal quantitative methods with cross-sectional design were used in this study. A total of 336 students from junior and senior high school were selected using cluster sampling technique. The research data was taken using the Generalized Problematic Internet Use Scale 2 (GPIUS2) instrument. The results showed that the average PIU level owned by students was in the medium category. Education and age levels also have a close correlation with the high level of PIU that students have. In addition there are internal and external factors that can cause students to be exposed to PIU. Thus, it is necessary to provide both preventive and curative counseling services that can help students formulate more potential activities in supporting students’ academic and social development. Keywords: Problematic internet use, prevalence, middle school